"Road Rash" and Dizziness: A Case of Hemodynamically Significant Topical Clonidine Toxicity. Issue 3 (26th February 2021) - Downs, John W; Cumpston, Kirk L
ABSTRACT: Clonidine is a central alpha-2 agonist well known to produce a syndrome of bradycardia and hypotension in overdose. However, few examples of overt clinical clonidine toxicity secondary to cutaneous absorption have been reported. We report a case of unintentional systemic clonidine toxicity in an adult because of a compounded preparation of clonidine applied to a degraded skin barrier. A 35-year-old male suffered a motorcycle accident 48 hours before presentation resulting in an abrasion to his distal left leg. On the day of presentation, he self-treated the wound by repeated application of a family member's pain-relieving cream. Later he was found confused and unable to stand by a family member. The family member recognized the thick visible coat of cream as the likely cause and decontaminated the patient while calling 911. Prehospital vitals were notable for a blood pressure of 80/30 mm Hg and heart rate of 38 beats per minute. In the emergency department, the patient was resuscitated with intravenous fluids with resultant normalization of blood pressure. Upon later review, the cream was determined to have been created by a local compounding pharmacy for the use in neuropathic pain and was labeled to contain clonidine, lidocaine, ketamine, and gabapentin. Cutaneous absorption of the pain cream was greatly increased because of loss of skin integrity. Military physicians and compounding pharmacies should ensure that patients are aware of the proper application of compounded creams and the potential risk for systemic toxicity with overuse or degraded skin.